Blend of low cost electrode material for energy storage device under DC glow discharge plasma exposed ESAC - Vijayalakshmi K.A; Judith Fennila; K T Maheswari (Zaštita Materijala)
The waste biomass in the form of eucalyptus globulus seeds activated carbon, which is employed as the electrode material and is environmentally acceptable, provides the good specific capacitance in the current work which is used for the energy storage application. A sample carbonization and physical activation procedure was used to create the activated carbon from the eucalyptus seeds. As prepared activated carbon was exposed to a DC glow discharge plasma, which modifies the surface of the material without altering its core characteristics. The investigation of the activated carbon was done utilizing structural, morphological, and electrochemical techniques of both pure and plasma treated. The increasing intensity of the X-ray diffraction indicates the carbon's amorphous and disorderly character. More oxygen-containing functional groups are present, according to an FTIR analysis. The FESEM/EDAX investigation has demonstrated the less appearance and more graphitic porosity with random orientation. Moreover, the electrochemical investigations were examined for utilization of the material of Electrochemical Impedance Spectroscopy (EIS) and Galvanostatic charge-discharge (GCD) which has a specific capacitance of 150F/g for a 1.5mA/g current density. The results revealed that the activated carbon made from Eucalyptus seeds after plasma treatment has good surface characteristics, improved specific capacitance, and is a low-cost electrode material for fabrication of energy storage device.